Phytochemical investigation of the flowers of Praxelis clematidea (Griseb.) R.M. King & H. Rob. Issue 20 (23rd September 2021) - Yang, Jian-Ni; Zhou, Xiu-Qiao; Nong, Xu-Hua; Cao, Jian; Hui, Yang; Wen, Mian; Chen, Wen-Hao
Abstract: Chemical investigations of the flowers of Praxelis clematidea resulted in the isolation of 12 known compounds (1 –12 ). Their structures were elucidated by extensive spectroscopic studies and chemical evidence. The structure and absolute configuration of 1 was precisely determined by a combination of 2 D NMR and quantum chemical calculations of ECD spectra analysis. Compounds 1, 4, 11 were isolated from the genus Praxelis for the first time, while 1 –6, 8 –12 were isolated from P. clematidea for the first time. The antibacterial activity of compounds 1, 2, 7, 9 were evaluated. Graphical Abstract: UF0001